Removal of total dissolved solids from wastewater using a revolving algal biofilm reactor. (3rd December 2019) - Peng, Juan; Kumar, Kuldip; Gross, Martin; Kunetz, Thomas; Wen, Zhiyou
Abstract: Total dissolved solids (TDS) comprising inorganic salts and organic matters are pollutants of concern to aquatic systems and water for human use. This work aimed to investigate the use of revolving algal biofilm (RAB) reactors as a sustainable and environmental friendly method to remove TDS from industrial effluents and municipal wastewaters. The wastewaters contained chloride, sodium, potassium, calcium, magnesium, and sulfate as the major components. The RAB reactors fed with synthetic industrial effluent with high TDS level demonstrated the best algal growth, with the highest TDS removal efficiency (27%) and removal rate (2, 783 mg/L‐day and 19, 530 mg/m 2 ‐day). A suspended algal culture system only removed 3% TDS from the same wastewater. The TDS removal by the RAB reactors was considered due to several mechanisms such as absorption by the algae cells, adsorption by extracellular polymeric substance of the biofilm, and/or precipitation. Collectively, this research shows that the RAB reactors can serve as an efficient system in wastewater remediation for TDS removal. Practitioner points: Total dissolved solids (TDS) in wastewater are pollutants of concern. The RAB reactors can remove TDS from various types of wastewater. The RAB reactors removed TDS by adsorbing ions elements such as Cl, Na, K, Ca, Mg, and S. The algal biomass absorbs ions through extracellular polymeric substance. Abstract : Revolving Algal Biofilm (RBA) reactor was used to treat wastewater with high content of total dissolved solids (TDS). RAB removed TDS from wastewater through precipitation, adsorption and absorption.